A green admixture for regulating mud slurry in sandy strata mud-water shield and its preparation method
By using admixtures composed of environmentally friendly raw materials such as green polymer materials in sandy formations, the slurry viscosity and pumpability are significantly improved, and the problem of insufficient viscosity during construction of mud and water shield structures in sandy formations is solved, and the dual goals of construction safety and ecological and environmental protection are achieved.
Patent Information
- Application Number
- CN202410942087.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-15
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-07-15
AI Technical Summary
In sandy formations, during the construction of mud-water shield, the existing technology is difficult to effectively increase the viscosity of the mud, resulting in the inability to effectively support the excavation surface, which poses a risk of collapse, and the existing admixtures have shortcomings in performance and ecological and environmental protection.
A sandy strata mud-water shield mud is used to regulate green admixture, which is composed of green polymer materials, environmentally friendly surfactants, cellulose derivatives, mineral blends, pumping agents and pH regulators. Through the combination of these raw materials, the viscosity of the mud is significantly improved and its pumping properties are improved.
This admixture can significantly increase the viscosity of the mud, ensure the safe and smooth implementation of the construction, and form a stable mud film in the sandy formation to improve the construction effect. At the same time, the raw materials used are all environmentally friendly materials, which can be gradually decomposed to meet the ecological and environmental needs.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of mud-water shield slurry regulation, and in particular relates to a green admixture for regulating mud-water shield slurry in sandy strata and a preparation method thereof. Background Art
[0002] With the development of society, urban rail transit has become one of the key construction projects of urban development. Slurry shield is widely used in rail construction due to its high degree of mechanization, fast construction speed, safety and reliability, and is constantly developing in the direction of large cross-section, deep burial and long distance. Sandy strata have low cohesion and poor stability. When slurry shield is excavated in such strata, accidents such as excavation face collapse are very likely to occur.
[0003] When the slurry shield is excavating, the slurry will penetrate in front of the excavation face under pressure, gradually blocking the pores and forming a mud film with low water permeability. However, in sandy strata and other strata with strong water permeability, it is often difficult for the slurry to form a mud film, and the excavation face cannot be effectively supported. For this reason, the engineering often increases the viscosity of the slurry to ensure the stability of the mud film.
[0004] CN 111484269 A discloses a viscosity regulator for cement-based grouting materials, wherein the water-soluble high molecular polymer includes one or a combination of two or more of starch, xanthan gum, guar gum, polyanionic cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, polyacrylamide, and partially hydrolyzed polyacrylamide. However, the viscosity regulator provided by the patent is for cement materials, and the patent limits the proportion and concentration of the materials and is not suitable for adjusting the viscosity of mud.
[0005] The slurry prepared with the materials disclosed in CN112851216A has a low viscosity and cannot meet the basic viscosity requirement of slurry film formation when the slurry shield is excavating in sandy strata. In addition, the materials used in this patent cannot meet environmental requirements.
[0006] CN 111663948 A aims at the problems of poor soil flow plasticity and difficulty in soil discharge during construction of earth pressure balance shield in water-rich sand and gravel strata, and provides an improved admixture for shield slag in water-rich sand and gravel strata. The material is only suitable for regulating the slag performance of earth pressure balance shield, and cannot regulate the mud performance of mud water shield, and does not take into account the needs of ecological protection.
[0007] The existing methods to increase mud viscosity are mainly to increase the bentonite content and add admixtures. However, adding too much bentonite will affect the pumping capacity of the mud, and the existing admixtures still have major deficiencies in performance and ecology. Therefore, how to develop a green admixture to ensure the green and safe construction of slurry shield is an important issue that needs to be solved urgently. Summary of the invention
[0008] In order to solve the above technical problems, the present invention proposes a green admixture for regulating mud in sandy strata mud-water shield and a preparation method thereof. The green admixture of the present invention can effectively increase the mud viscosity, and the raw materials used are all environmentally friendly materials, which can meet the needs of shield construction.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] One of the technical solutions of the present invention:
[0011] A green admixture for regulating slurry of a mud shield in a sandy formation, comprising the following raw materials in parts by mass:
[0012] 40-70 parts of green polymer materials, 10-15 parts of environmentally friendly surfactants, 5-10 parts of cellulose derivatives, 2-5 parts of mineral admixtures, 2-3 parts of pumping agents and 3-8 parts of pH regulators.
[0013] The admixture of the present invention can significantly increase the viscosity of the mud, ensuring the safe and smooth implementation of the construction. The improved mud can form a stable mud film in the sandy stratum, thereby improving the improvement effect. In addition, the components of the mud regulation green admixture provided by the present invention are all green and pollution-free, and can be gradually decomposed over time.
[0014] Preferably, the green admixture for regulating slurry of mud shield in sandy formations comprises the following raw materials, calculated by weight: 40-50 parts of green polymer materials, 10-12 parts of environmentally friendly surfactants, 5-7 parts of cellulose derivatives, 2-3 parts of mineral admixtures, 2 parts of pumping agents and 3-5 parts of pH regulators.
[0015] More preferably, the green admixture for regulating slurry of mud shield in sandy formations comprises the following raw materials, calculated by weight: 50 parts of green polymer materials, 12 parts of environmentally friendly surfactants, 7 parts of cellulose derivatives, 3 parts of mineral admixtures, 2 parts of pumping agents and 5 parts of pH regulators.
[0016] Preferably, the green polymer material is a mixture of guar gum, xanthan gum and anionic polyacrylamide (PAM), and the mass ratio of the three is 2:2:1-3:4:1, preferably 2:2:1. Guar gum and xanthan gum are natural polysaccharide natural polymers, and adding them to the mud can effectively increase the viscosity of the mud. Anionic polyacrylamide is a low-toxic water-soluble polymer with good biocompatibility. Within the scope defined by the present invention, guar gum and xanthan gum can be fully mixed with anionic polyacrylamide, and the viscosity of the mixture is the highest.
[0017] Preferably, the guar gum is a highly esterified guar gum with a mesh size between 60 and 80. Too large or too small a mesh size of the guar gum will affect the mixing effect of the materials and the uniformity of the material dispersion. Within the above mesh size range, the materials can have the best mixing effect.
[0018] Preferably, the xanthan gum is standard xanthan gum with a mesh size between 80 and 100 meshes.
[0019] Preferably, the hydroxyl groups in the highly esterified guar gum molecules are formylated groups, which have good water solubility and strong gelling properties.
[0020] Preferably, the number average molecular weight of the anionic polyacrylamide is between 10 and 12 million, and the pH is between 6.5 and 8. Anionic polyacrylamide with a higher molecular weight has a better viscosity-increasing effect. However, anionic polyacrylamide with a molecular weight that is too high may cause the mud to be too viscous, affecting subsequent processing. Under different pH conditions, the surface charge state of the suspended particles in the mud will change, thereby affecting the interaction between PAM and the particles. In this pH range, anionic polyacrylamide has better solubility and the strongest viscosity-increasing effect.
[0021] Preferably, the environmentally friendly surfactant is a mixture of fatty acid methyl ester sulfonate and alkyl glycoside, and the mass ratio of the two is 1:1-1:2, preferably 1:2. The mixture of fatty acid methyl ester sulfonate and alkyl glycoside can reduce the irritation of the material and produce a significant synergistic effect. When the surfactant molecules are adsorbed on the surface of the mud, the hydrophilic group extends to the water, and the hydrophobic group is exposed to the outside, forming a surface layer in which the hydrophobic group is relatively concentrated. This arrangement reduces the interaction between the hydrophobic groups on the liquid surface, reduces the energy of the liquid surface, reduces the surface tension, improves the fluidity, stability and wettability of the mud, and increases the binding force with the formation. In addition, when the surfactant is used in conjunction with the green high molecular polymer, the surfactant is adsorbed on the molecular structure of the polymer, thereby increasing its viscosity.
[0022] Preferably, the cellulose derivative is at least one of hydroxyethyl cellulose, methyl cellulose, carboxymethyl cellulose and hydroxypropyl cellulose, and more preferably carboxymethyl cellulose. The addition of cellulose derivatives can greatly improve the fluidity of mud and help mud penetrate the formation, especially carboxymethyl cellulose has the best effect. In addition, the cellulose derivative is used in conjunction with a pumping agent to further increase the pumpability of mud.
[0023] Preferably, the mineral admixture is at least one of fly ash, limestone powder, steel slag powder and slag powder, more preferably a mixture of fly ash and slag powder, with a mass ratio of 1:2.
[0024] Preferably, the fly ash is Class C fly ash, which is high-calcium fly ash collected from calcining lignite or sub-bituminous coal, and its calcium oxide content is generally greater than 10%; the slag powder is granulated blast furnace slag powder, which mainly contains components such as calcium oxide and silicon oxide.
[0025] Preferably, the pumping agent is at least one of polyethylene glycol, methoxy polyethylene glycol, polypropylene glycol, polysorbate and polycarboxylic acid, more preferably polyethylene glycol and polypropylene glycol, and the mass ratio of the two is 2: 1. The addition of the pumping agent increases the pumpability of the mud. In addition, when the pumping agent is compounded with the green polymer material at this ratio, the mechanical properties of the mud film can be effectively improved, achieving the best synergistic optimization effect.
[0026] Preferably, the pH regulator is soda ash (i.e., sodium carbonate). The addition of the pH regulator can increase the viscosity of the mud. In the present invention, the pH is controlled between 7.5 and 8.0. Within this range, the mud viscosity can reach the highest, and the preferred pH is 7.5. If the pH value is greater than 8, it is an alkaline substance, which will cause the polar groups of the polymer to fall off, affecting the viscosity.
[0027] The second technical solution of the present invention:
[0028] The present invention also provides a method for preparing the green admixture for regulating slurry of a mud shield in sandy strata, comprising the following steps:
[0029] Weigh the raw materials according to the ratio, add the green polymer material and the cellulose derivative into water, stir until dissolved, add the pH adjuster to adjust the pH to 7.5-8.0, add the mineral admixture and the environmentally friendly surfactant, stir until dissolved, add the pumping agent, stir until dissolved, and obtain the green admixture for regulating the mud slurry of the sandy formation mud shield.
[0030] Preferably, the stirring speed is controlled to be 60-100 revolutions per minute during stirring.
[0031] The third technical solution of the present invention:
[0032] The present invention also provides the use of the green additive for regulating sandy stratum mud-water shield slurry in preparing sandy stratum mud-water shield slurry.
[0033] Preferably, the injection rate of the green admixture for regulating sandy formation mud-water shield slurry is 3-5% when preparing sandy formation mud-water shield slurry.
[0034] Compared with the prior art, the present invention has the following advantages and technical effects:
[0035] (1) The green admixture for regulating mud slurry in sandy strata of the present invention can significantly increase the viscosity of the mud, ensure the safe and smooth implementation of the construction, and the improved mud can form a stable mud film in the sandy strata. At the same time, the addition of the pumping agent of the present invention increases the pumpability, can effectively reduce the risk of pipe blockage, and improves the improvement effect. The components of the green admixture for regulating mud slurry in sandy strata provided by the present invention are all green and pollution-free, and can be gradually decomposed over time.
[0036] (2) The preparation method of the green admixture for regulating the slurry of the mud shield in sandy strata of the present invention is simple and easy to promote and use. DETAILED DESCRIPTION
[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0038] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0039] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0040] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0041] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0042] All raw materials used in the embodiments of the present invention are purchased from commercial sources. As an example, high-esterified guar gum is purchased from Shandong Hongyu Engineering Technology Co., Ltd.
[0043] Unless otherwise specified, the “parts” used in the embodiments of the present invention refer to “parts by mass”.
[0044] In the embodiment of the present invention, the mud used in the test is bentonite mud, which is prepared by itself, and the preparation ratio is water: sodium-based bentonite = 50:1 (mass ratio).
[0045] The soda ash in the embodiment of the present invention is sodium carbonate.
[0046] The technical solution of the present invention is further illustrated by the following embodiments.
[0047] Example 1
[0048] 50 parts of green polymer materials (a mixture of high esterified guar gum (70 mesh), xanthan gum (90 mesh) and anionic polyacrylamide (number average molecular weight of 11 million, pH of 6.5) in a mass ratio of 2:2:1) and 7 parts of cellulose derivative (carboxymethyl cellulose) were added to 100 parts of water, stirred to dissolve, and 5 parts of pH regulator (soda ash) were added to adjust the pH to 7.5, and 3 parts of mineral admixture (C type fly ash and granulated blast furnace slag powder in a mass ratio of 1:2 The mixture is composed of 1:1 and 12 parts of surfactant (a mixture of fatty acid methyl ester sulfonate and alkyl glucoside in a mass ratio of 1:2), the stirring speed is controlled at 70 revolutions per minute, and the mixture is stirred to be evenly dissolved. Then 2 parts of pumping agent (a mixture of polyethylene glycol and polypropylene glycol in a mass ratio of 2:1) are added, and the mixture is stirred to be fully dissolved to obtain a green admixture for regulating mud of sandy strata mud-water shield (hereinafter referred to as "admixture"), and the prepared admixture is injected into the experimental mud (injection rate is 3%).
[0049] Example 2
[0050] 60 parts of green polymer materials (a mixture of highly esterified guar gum (80 mesh), xanthan gum (100 mesh) and anionic polyacrylamide (number average molecular weight of 12 million, pH of 7.5) in a mass ratio of 3:4:1) and 10 parts of cellulose derivatives (a mixture of hydroxyethyl cellulose and methyl cellulose in a mass ratio of 1:1) are added to 100 parts of water, stirred to dissolve, and 5 parts of pH adjuster (soda ash) are added to adjust the pH to 8, 4 parts of mineral admixtures (a mixture of limestone powder and steel slag powder in a mass ratio of 1:2) and 14 parts of surfactants (a mixture of fatty acid methyl ester sulfonate and alkyl glycoside in a mass ratio of 1:1) are added, the stirring speed is controlled at 80 revolutions per minute, stirred to dissolve evenly, and then 2 parts of pumping agent (methoxy polyethylene glycol) are added and stirred to fully dissolve to obtain an admixture, and the prepared admixture is injected into the experimental mud (injection rate is 3%).
[0051] Example 3
[0052] 70 parts of green polymer materials (a mixture of high esterified guar gum (60 mesh), xanthan gum (80 mesh) and anionic polyacrylamide (number average molecular weight of 11 million, pH of 6.5) in a mass ratio of 2:2:1) and 6 parts of cellulose derivatives (hydroxypropyl cellulose) are added to 100 parts of water, stirred to dissolve, and 3 parts of pH adjuster (soda ash) are added to adjust the pH to 8, 2 parts of mineral admixtures (a mixture of Class C fly ash and granulated blast furnace slag powder in a mass ratio of 1:2) and 15 parts of surfactants (a mixture of fatty acid methyl ester sulfonate and alkyl glycoside in a mass ratio of 1:2) are added, the stirring speed is controlled at 70 revolutions per minute, stirred to dissolve evenly, and then 2 parts of pumping agents (a mixture of polysorbate and polycarboxylic acid in a mass ratio of 2:1) are added and stirred to fully dissolve to obtain an admixture, and the prepared admixture is injected into the experimental mud (injection rate is 3%).
[0053] Example 4
[0054] 50 parts of green polymer materials (a mixture of high esterified guar gum (70 mesh), xanthan gum (90 mesh) and anionic polyacrylamide (number average molecular weight of 11 million, pH of 6.5) in a mass ratio of 2:2:1) and 5 parts of cellulose derivatives (carboxymethyl cellulose) are added to 100 parts of water, stirred to dissolve, and 8 parts of pH adjusters (soda ash) are added to adjust the pH to 8, 5 parts of mineral admixtures (a mixture of Class C fly ash and granulated blast furnace slag powder in a mass ratio of 1:2) and 10 parts of surfactants (a mixture of fatty acid methyl ester sulfonate and alkyl glycoside in a mass ratio of 1:2) are added, the stirring speed is controlled at 70 revolutions per minute, stirred to dissolve evenly, and then 3 parts of pumping agents (a mixture of polyethylene glycol and polypropylene glycol in a mass ratio of 2:1) are added, stirred to fully dissolve, and an admixture is obtained, and the prepared admixture is injected into the experimental mud (injection rate is 5%).
[0055] Comparative Example 1
[0056] The only difference from Example 1 is that the green polymer material is replaced by a common polymer material (anionic polyacrylamide) on the market.
[0057] Comparative Example 2
[0058] The only difference from Example 1 is that the addition of the pH adjuster is omitted.
[0059] Comparative Example 3
[0060] The only difference from Example 1 is that the addition of surfactant is omitted.
[0061] Comparative Example 4
[0062] The only difference from Example 1 is that the high-esterified guar gum is replaced by an equal amount of guar gum, that is, the guar gum in this comparative example does not contain a formylated group.
[0063] Comparative Example 5
[0064] The only difference from Example 1 is that the environmentally friendly surfactant is alkyl polyglycoside.
[0065] Comparative Example 6
[0066] The only difference from Example 1 is that the mass ratio of the mixture of guar gum, xanthan gum and anionic polyacrylamide in the green polymer material is 4:4:1.
[0067] Comparative Example 7
[0068] The only difference from Example 1 is that the mass ratio of the mixture of guar gum, xanthan gum and anionic polyacrylamide in the green polymer material is 1:1:4.
[0069] Effect verification
[0070] The slurries prepared in Examples 1-4 and Comparative Examples 1-7 were tested for viscosity, pumpability, biodegradability and biotoxicity:
[0071] The viscosity test adopts GB / T 10247-2008 standard and uses a rotational viscometer for testing;
[0072] The specific test method for pumpability is: refer to ASTM D1092 standard;
[0073] The test method for biodegradability is: refer to the relevant standards of the International Organization for Standardization (ISO), ISO 14855-1:2012;
[0074] The test method of biological toxicity is as follows: the mud sample to be evaluated is sampled and tested; after stirring and centrifuging the test sample, the upper sample liquid is taken, and the upper sample liquid is diluted into sample liquids of different concentrations as the test group; 2.0mL of 3wt% sodium chloride solution is added to the test tube of the control group; then luminescent Escherichia coli liquid is added to the test tubes of the test group and the control group respectively, and the mud half-lethal concentration value is obtained according to the respective luminescence amounts, and the mud toxicity is evaluated based on the mud half-lethal concentration value;
[0075] The test method for film-forming performance is: first place standard sand in the infiltration device as the infiltration formation, then add the mud mixed with admixtures, and after 30 minutes, observe the film-forming performance of the mud.
[0076] The test results are shown in Table 1.
[0077] Table 1
[0078] Viscosity(mPa*s) Pumpability(g / min) 45-day biodegradation rate (%) <![CDATA[EC 50 (mg / L)]]> Film forming properties Example 1 52 40 87 1623 Excellent Example 2 45 42 85 1620 Excellent Example 3 50 41 82 1520 Excellent Example 4 48 45 82 1590 Excellent Comparative Example 1 26 34 76 980 Poor Comparative Example 2 32 35 74 1210 generally Comparative Example 3 36 36 73 1310 generally Comparative Example 4 38 34 73 1201 Poor Comparative Example 5 39 36 72 1320 Poor Comparative Example 6 41 38 78 1340 generally Comparative Example 7 40 39 80 1320 generally
[0079] Note: In Table 1, “excellent” film-forming performance refers to a dense mud skin film with a fast formation speed; “average” refers to a mud skin + permeability zone type mud film with a moderate formation speed, with a small amount of mud penetrating into the formation; and “poor” refers to a permeability zone type mud film with a moderate formation speed, with most of the mud penetrating into the formation.
[0080] It can be seen from Table 1 that the admixtures of various embodiments of the present invention can effectively improve the viscosity of the mud shield slurry in sandy formations, and the raw materials used are all environmentally friendly materials, which can meet the needs of shield construction. The green polymer material of Comparative Example 1 is a common polymer material (anionic polyacrylamide) on the market. The material has a low viscosity and a low biodegradation rate when used alone. The present invention improves the biodegradation rate by mixing it with other raw materials; Comparative Example 2 omits the addition of a pH regulator, and the pH in the mud is not adjusted. Under this environment, the viscosity of the mud is not maximized, and the film-forming performance is general; Comparative Example 3 omits the addition of a surfactant, lacks the synergistic effect of the surfactant and the green polymer material, so the viscosity is low; Comparative Example 4 replaces the addition of high-esterified guar gum with ordinary guar gum. The high-esterified guar gum molecules have good water solubility and strong gelling property. The lack of high-esterified guar gum causes the viscosity to decrease; Comparative Example 5 changes the surfactant only to an alkyl glucoside instead of a mixture of fatty acid methyl ester sulfonate and alkyl glucoside, which slightly reduces the viscosity of the mud and has poor film-forming property; Comparative Examples 6 and 7 change the proportion of green polymer materials, and the mud viscosity is not good under this proportion.
[0081] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. Application of a green admixture for regulating mud shield slurry in sandy formations in preparing mud shield slurry in sandy formations, characterized in that: The green admixture for regulating slurry of mud shield in sandy formation comprises the following raw materials in parts by mass: 40-70 parts of green polymer materials, 10-15 parts of environmentally friendly surfactants, 5-10 parts of cellulose derivatives, 2-5 parts of mineral admixtures, 2-3 parts of pumping agents and 3-8 parts of pH regulators; The green polymer material is a mixture of guar gum, xanthan gum and anionic polyacrylamide; The guar gum is high-esterified guar gum; The number average molecular weight of the anionic polyacrylamide is between 10 and 12 million, and the pH is between 6.5 and 8; The environmentally friendly surfactant is a mixture of fatty acid methyl ester sulfonate and alkyl glycoside; The cellulose derivative is at least one of hydroxyethyl cellulose, methyl cellulose, carboxymethyl cellulose and hydroxypropyl cellulose; The mineral admixture is at least one of fly ash, limestone powder, steel slag powder and slag powder; The pumping agent is at least one of polyethylene glycol, methoxy polyethylene glycol, polypropylene glycol, polysorbate and polycarboxylic acid; The pH adjuster is soda ash.
2. A method for preparing a green admixture for regulating mud shield slurry in sandy strata, characterized in that: The green admixture for regulating mud slurry in sandy formation is the green admixture for regulating mud slurry in sandy formation in claim 1, comprising the following steps: Weigh the raw materials according to the ratio, add the green polymer material and the cellulose derivative into water, stir until dissolved, add the pH adjuster to adjust the pH to 7.5-8.0, add the mineral admixture and the environmentally friendly surfactant, stir until dissolved, add the pumping agent, stir until dissolved, and obtain the green admixture for regulating the mud slurry of the sandy formation mud shield.
Citation Information
Patent Citations
Viscosity regulator for cement-based grouting material and preparation method thereof
CN111484269A
High-water-retention low-viscosity pipe jacking thixotropic slurry
CN112851216A
Water-rich sand pebble stratum shield muck improvement additive and preparation method thereof
CN111663948A